2017
DOI: 10.2169/internalmedicine.56.7728
|View full text |Cite
|
Sign up to set email alerts
|

Platypnea-orthodeoxia Syndrome in a Patient with an Atrial Septal Defect: The Diagnosis and Choice of Treatment

Abstract: A 77-year-old woman developed dyspnea over three years which occurred during sitting, standing or walking. Her physical examination, chest X-ray, ECG and cardiac catheterization results were all normal. A marked fall in arterial oxygen saturation was observed on sitting or standing. Transesophageal echocardiography showed an increase of right to left shunt flow on sitting. The patient was diagnosed with platypnea-orthodeoxia syndrome and underwent the surgical closure of an atrial septal defect of 19 mm in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Among cardiac causes, patent foramen ovale is the most frequent lesion and ASD ranks second [4]. TEE, the preferred diagnostic study to visualize cardiac defects or aneurysms, confirmed an ostium secundum ASD in this patient.…”
Section: Discussionmentioning
confidence: 59%
“…Among cardiac causes, patent foramen ovale is the most frequent lesion and ASD ranks second [4]. TEE, the preferred diagnostic study to visualize cardiac defects or aneurysms, confirmed an ostium secundum ASD in this patient.…”
Section: Discussionmentioning
confidence: 59%
“…Our findings reinforce the hypothesis that, due to their geometry and anatomic proximity, the aortic root dilation could increase ASM. This mechanism was already postulated in case reports of patients with platypnea–orthodeoxia syndrome (Kazawa et al, 2017 ).…”
Section: Discussionmentioning
confidence: 66%
“…Our findings reinforce the hypothesis that, due to their geometry and anatomic proximity, the aortic root dilation could increase ASM. This mechanism was already postulated in case reports of patients with platypnea-orthodeoxia syndrome (Kazawa et al, 2017). Aortic atherosclerosis and dilation are also associated with cardiovascular risk factors and vascular clinical events (Gardin et al, 2006).…”
Section: Discussionmentioning
confidence: 77%
“…Subsequently, right-to-left shunt must be confirmed. TEE is crucial for direct visualization of the shunt flow or structural abnormalities and has been used in some reported cases (4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…It is reportedly caused by right-to-left shunt, which is augmented by anatomical changes in the upright posture (2). A small number of cases of POS have been reported (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), and their pathogenesis is complex and not uniform.…”
Section: Introductionmentioning
confidence: 99%